Analyzing the Space–Time Dynamics of Innovation in China: ESDA and Spatial Panel Approaches. (22nd July 2015) - Wang, Zheye; Cheng, Yeqing; Ye, Xinyue; Wei, Y. H. Dennis
Abstract: Through applying exploratory spatial data analysis (ESDA) and confirmatory spatial data analysis (CSDA), this paper examines the space–time dynamics of innovation at the provincial level in China from 2000 to 2011. We first investigate the trend of regional inequality in innovation in China and then use ESDA methods to visualize the space–time relationship between patent applications and innovation determinants. Impacts of innovation determinants on the space–time dynamics of innovation are also examined by analyzing the knowledge production function with the spatial panel Durbin model. Knowledge spillovers from both the R&D and the innovation outcome perspectives are highlighted in CSDA. We have found an increasingly intensified coastal–interior divide with growing spatial clusters and more innovative activities in the coastal region. We have also found a close space–time relationship between innovation and its determinants. Lastly, innovation spillovers cross province boundaries, and knowledge from a province's neighboring provinces has substantial effects on innovation activities of the province. This paper highlights positive knowledge spillover effects between regions, the close relationship between innovation and its determinants, and the importance of spatial externalities in innovation activities.